Środki unijne w finansowaniu infrastruktury komunalnej na przykładzie gmin powiatu gliwickiego - Kukla, Bogusława (European Union Resources in Financing of Communal Infrastructure on the Example of Communes from Gliwice District, 2006)
In the framework of the policies of cohesion, the European Union supports poorer member countries. These countries may get help which supports their development. The main purpose of regional policy is comprehensive affirmation of harmonious development of the whole union, first of all, escalation of degree of economic, spatial and social cohesion of their countries and regions, as well as cutting the limitation of internal differences in the development. From early 90's also Poland gains access to EU's direct financial and technical support. In that time programs, so-called pre-accession funds, which support aims of regional politics, were implemented. The main source of the support of environmental communal investments in the years 1999-2003 were the following programs: PHARE, SAPARD and ISPA, which in participation of domestic funds enable the realization of many investments of communal infrastructure. The accession to the European Union cuts Poland from the access to Structural Funds and Cohesion Funds - which are most important tools of structural (regional) politics. Support will be also given in the framework of the EEA Financial Mechanism and the Norwegian Financial Mechanism. At this moment these founds are waiting for startup. The aim of this article is to show the European Union resources which are accessible for financing of communal infrastructure in the pre-accessing period of time and after the accession of Poland to the European Union. Exemplification is related to the communes from the Gliwice district.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 459-469